Slum-dwelling Children Community Engagement by Tertiary Sociology Students of Rajshahi University: A Beneficiary Approach to Learning - Md. Mithu Rana; Md. Shahidul Islam; Md. Ariful Islam (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2022)
The study has focused on the condition of children in the community, initiatives of tertiary sociology students for successful engagement, changes of the slum-dwelling children, and attainment of graduate and professional skills. A mixed-method of social survey, FGDs (Focus Group Discussion), and participant observation with close and open-ended questionnaires, face-to-face interviews, checklists, and Likert scale techniques have been used to collect primary data. The findings of the study show that students’ engagement helps to meet children’s educational, socialization, health care, and co-curricular needs and rights and some other needs of community people. It brings benefits for engaged students building stronger relations with graduate institutions, different organizations, and job providers, and attaining several graduate and professional skills, and abilities to become successful in personal and professional life.